Association between Adherence to SSRI Treatment and Mortality among Individuals with Metabolic Syndrome Components - Avrahamy, Hamutal; Shoval, Gal; Hoshen, Moshe; Balicer, Ran D.; Kamhi-Nesher, Shiri; Zalsman, Gil; Weizman, Abraham; Krivoy, Amir (Pharmacopsychiatry, 2021)
Introduction Depression and anxiety have been associated with type 2 diabetes mellitus and metabolic syndrome, major causes of cardiovascular morbidity and mortality. The effect of antidepressants in this association is unknown. This study aimed to examine the association between adherence to selective serotonin receptor inhibitors (SSRIs) and all-cause mortality among individuals with metabolic syndrome components (hypertension, obesity, and diabetes mellitus).Methods Data on 201 777 patients who were prescribed SSRIs during the years 2008–2011 were analyzed retrospectively. Adherence was measured using prescription purchase records. The moderating effect of SSRI and statin adherence on the association between metabolic syndrome load and mortality hazard risk (HR) during the study period were analyzed. The Cox-proportional hazard model adjusted to background variables was used to this end.Results During the study period, the maximal metabolic load was associated with mortality HR=1.89 (95% CI: 1.79–2) compared to participants without metabolic risk factors. A slight reduction in mortality HR was demonstrated among those with low and moderate SSRI adherence rates. Adherence to statins was negatively associated with the risk of mortality across all levels of adherence. A significant association (r=0.214, p<0.01) was found between adherence to statins and adherence to SSRIs, with higher rates of adherence to statins across all metabolic load categories.Discussion While a high metabolic load is associated with a higher risk of mortality, adherence to SSRIs only partially moderated the risk of mortality, in contrast to the protective effect of statins. Adherence differences to statins and SSRIs among individuals prescribed both medications merit further investigation.
Keywords: antidepressants; all-cause mortality; adherence; psychopharmacology; pharmacoepidemiology